P102 Discordant exudative pleural effusions: demographics and aetiology. (12th November 2019) - Addala, D; Mercer, RM; Lu, Q; Shepherd, G; Castro, O; Varatharajah, R; Thayanandan, A; Hassan, M; Bedawi, E; Mccracken, D; Asciak, R; Tsikrika, M; et al.
Abstract : Introduction: Light's criteria is widely utilised to differentiate pleural effusions as exudative or transudative. In a subsect of pleural effusions, there is discordance between protein and lactate dehydrogenase (protein high, LDH low or vice versa). The causes of this biochemical pattern are not well established, nor are the mechanisms well understood. Objectives: To establish the incidence of discordant pleural effusions, and determine demographics and common aetiologies leading to discordance. Methods: We performed a retrospective analysis of initial pleural fluid samples sent between 2015–2017 (n=995) from a UK tertiary centre. 792 of these were exudative based on Light's criteria. These were subdivided into concordant or discordant exudates, with analysis of demographics and final diagnoses in each group. Low protein was defined as <30g/L and low LDH <170IU/L according to local assays. Results: 29% (n= 229) of exudative effusions displayed discordance in either LDH or protein. 33% of these (n=75) had low protein with high LDH and 67% (n= 154) had low LDH with high protein. The median age was significantly higher in the discordant group (75 years vs 70 years). In the discordant group with high protein, the most common diagnoses were malignant pleural effusion (MPE) 38% (n=59), cardiac/osmotic related effusions 13% (n=19), and infection 7% (n=12). The most common diagnoses in the discordant group with high LDH were infection 37% (n=30), MPE 24% (n=18), and cardiac/osmotic related 7% (n=6). In the concordant group (n=486), frequent diagnoses were MPE 42% (n=206), Infection 37% (n=132) with cardiac/osmotic related effusions only representing <2% (n=8). Figure 1 compares the percentage occurrence of specific diagnoses in concordant and discordant groups. Conclusions: A significant proportion of pleural effusions that are initially classified as exudative display discordance between LDH and protein. Discordance occurs in older patients, possibly due to increased capillary permeability with age. Within discordant groups, more effusions occurred secondary to global fluid overloaded states (11% of discordant versus <2% concordant). Further analysis beyond Light's criteria is warranted, particularly with increasing age. In patients with discordant pleural fluid, attention should be paid to cardiac and renal investigations to ensure the correct aetiology is determined.